"Expand and Click": A New Method for Labeling HIV-1 Envelope Glycoproteins. Issue 5 (18th May 2017) - Fernandez, Melissa V.; Freed, Eric O.
Abstract : In this issue of Cell Chemical Biology, Sakin et al. (2017) investigate the nanoscale behavior of the HIV-1 envelope (Env) glycoprotein complex by using genetic code expansion, bioorthogonal amino acids, synthetic dyes, and click chemistry. This minimally invasive approach allows the measurement of native Env cellular distribution and dynamics. Abstract : In this issue of Cell Chemical Biology, Sakin et al. (2017) investigate the nanoscale behavior of the HIV-1 envelope (Env) glycoprotein complex by using genetic code expansion, bioorthogonal amino acids, synthetic dyes, and click chemistry. This minimally invasive approach allows the measurement of native Env cellular distribution and dynamics.